Cognitive impairment and diabetic control among elderly type II diabetic mellitus in HUSM - Khathri, Khairunnisa Mohd (2016)
Introduction: This study aims, looked at the proportion of diabetic control and cognitive impairment, and its association among elderly Type II diabetes Mellitus in HUSM. As the elderly population in our country and diabetes keep increasing to determine proportion and its associations is important to see our population disease trend. Increase number of ageing people with diabetes will increase our health care burden, thus hopefully it will help in managing geriatric with diabetes population. Objective: This is a cross sectional study to determine the proportion of cognitive impairment and diabetes control and their association among elderly diabetes in HUSM Methods: It’s involved 403 patient type 2 DM who attending Klinik Rawatan Keluarga HUSM, age more than 60. This study was conducted from August 2013 until May 2014. Self-administrated questionnaire were given for data collection. Patients were screen for depression then they were put into systematic random sampling 1 in 2. The questionnaires that were used in this study consist of socio-demographic data, and Malay version Diabetes Knowledge questionnaire. Hba1c 7 and below was used to determine diabetes control and Mini Mental State Examination Malay version was used to asses cognitive impairment. Result: The proportion of diabetic control in this study based on Hba1c level 7% and below was 25% and 4.0% found to have cognitive impairment. There is no association between cognitive impairment and diabetes control. The mean score of diabetes knowledge questionnaire is 12.9. Conclusion: From this study, the diabetes control was quiet good compared to other study in this country, but still below national standard and low proportion of cognitive impairment. There is no association between cognitive impairment and diabetes control may due to low proportion of cognitive impairment.